On Complementable Semihypergroups. Issue 4 (2nd April 2016) - Aghabozorgi, Hossien; Cristea, Irina; Jafarpour, Morteza
Abstract : In this article, we first introduce the notion of complementable semihypergroup, proving that the classes of simplifiable semigroups, groups, simplifiable semihypergroups, and complete hypergroups are examples of complementable semihypergroups. Then we define when two semihypergroups are disjoint and find examples of such semihypergroups. Finally, we discuss on the complementable property of K H -hypergroups.